Conformational states of HAMP domains interacting with sensory rhodopsin membrane systems: an integrated all-atom and coarse-grained molecular dynamics simulation approach. Issue 1 (30th November 2016) - Sahoo, Bikash Ranjan; Fujiwara, Toshimichi
Abstract : The mechanistic and structural basis of srII–htrII signaling mediated by a HAMP four-helix bundle in Natronomonas pharaonis . Abstract : Understanding the downstream signaling mechanism of sensory rhodopsin and its cognate transducer complex (srII–htrII) has long been a challenge in the field of photoreceptor research. Here, an integration of all-atom and coarse-grained (CG) molecular dynamics (MD) simulations in different srII–htrII complex states is carried out. It is shown that the cytoplasmic four-helix HAMP dimer gives rise to a gear-box model interaction with discrete hydrophobic packing in Natronomonas pharaonis ( Np ). Structural analysis in all-atom and CG-MD reveals a stable conformational state in the physiological environment (323 K and 1.15 M salt). Comparative analysis in the ground and intermediate state conformations reveals substantial inter-HAMP interactions in the intermediate state with uniform clockwise (+10° to +30°) and counterclockwise (−20° to −40°) rotations in the α1 helix and the α2 helix of the monomer, respectively. Low temperature and low salt environments (283 K and 0.15 M) significantly affect srII–htrII binding affinity in both states with unusual helix bending. The distinguished control cable, knob-into-holes packing and piston-like movements in HAMP helices are found in the intermediate state complex. The N-terminal htrII (159 residues) coupled with srII yields a binding energy (Δ G bind ) of −309.22, −436.53 and −331.11 kJ mol −1 in the MM/PBSA calculation for the Np htrII homodimer, the Np srII–htrII ground state conformation and the Np srII–htrII intermediate state conformation, respectively. Only the HAMP1 domain shows a very low Δ G bind value (−21.03 kJ mol −1 ) for the ground state in comparison to that for the intermediate state (−54.68 kJ mol −1 ). The structural analysis highlights the key residues that include Y199 srII, T189 srII, E43 htrII, T86 htrII, M100 htrII, E116 htrII, E126 htrII and S130 htrII for complex stabilization and signal transduction.